A Pharmacogenetic Study of CYP2C19 in Acute Coronary Syndrome Patients of Colombian Origin Reveals New Polymorphisms Potentially Related to Clopidogrel Therapy - Angulo-Aguado, Mariana; Panche, Karen; Tamayo-Agudelo, Caroll Andrea; Ruiz-Torres, Daniel-Armando; Sambracos-Parrado, Santiago; Niño-Orrego, Maria Jose; Páez, Nathaly; Piñeros-Hernandez, Laura B; Castillo-León, Luisa-Fernanda; Pardo-Oviedo, Juan Mauricio; Abaunza, Katherine Parra; Laissue, Paul; et al. (Journal of personalized medicine, 2021)
Clopidogrel, an oral platelet P2Y12 receptor blocker, is used in the treatment of acute coronary syndrome. Interindividual variability in treatment response and the occurrence of adverse effects has been attributed to genetic variants in CYP2C19. The analysis of relevant pharmacogenes in ethnically heterogeneous and poorly studied populations contributes to the implementation of personalized medicine. We analyzed the coding and regulatory regions of CYP2C19 in 166 patients with acute coronary syndrome (ACS) treated with clopidogrel. The allele frequencies of CYP2C19 alleles *1, *2, *4, *17, *27 and *33 alleles were 86.1%, 7.2%, 0.3%, 10.2%, 0.3% and 0.3%, respectively. A new potentially pathogenic mutation (p.L15H) and five intronic variants with potential splicing effects were detected. In 14.4% of the patients, a new haplotype in strong linkage disequilibrium was identified. The clinical outcome indicated that 13.5% of the patients presented adverse drugs reactions with a predominance of bleeding while 25% of these patients were carriers of at least one polymorphic allele. We propose that new regulatory single-nucleotide variants (SNVs) might potentially influence the response to clopidogrel in Colombian individuals.